Studi Kasus Implementasi Metode Lean Startup pada UMKM Industri Makanan “MEN” - Maria Yvonne Hidajat; Lamtiur Hasianna Tampubolon; Heru Prasadja (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
In the era of rapid technological developments, companies are increasingly required to compete in goods and services markets more efficiently and effectively. Therefore choosing the most fit entrepreneurial method will play an important role in the sustainability and success of the company. One entrepreneurial method that is currently starting to get attention in the business world is the Lean Startup method. This research examines the description of Lean Startup method implementation in food catering MSME company "MEN". This research was conducted using a qualitative case study method which aims to explore in depth a concept in a particular context and environment. The results of the research show that the food catering MSME "MEN" implements the Lean Startup method through a fairly simple system, such as a pre-order system, verbal consumer feedback, and evaluations accompanied by adjustments to business activities. With this simple system, business actors can minimize and increase the effectiveness of the company's initial investment and costs. This research provides new insight of how a simple and widely used tool can be used as a tool in carrying out the Lean Startup method which is generally closely related to the image of advanced technology.